Factibilidad para la creación de un restaurant de mariscos en el cantón Ventanas, año 2014 - Ramírez Vecilla, Iliana Raquel (2015)
This research was established with the primary purpose of analyzing the feasibility of creating a seafood restaurant in Canton Windows, through the analysis of supply and demand through the realization of market research, compiling the relevant aspects according to the needs of the demand for the creation of the restaurant and performing technical study - Financial to analyze the feasibility of implementing the investment. In developing research states that the market survey in the canton Windows, through the survey, aimed at Canton 243 inhabitants according to the applied sample and 2 interviews seafood restaurant owners. Besides the technical study detailing the different aspects such as location, size of the restaurant facilities, including technical human resources and other factors also established. The feasibility is established it in the financial economic study and where the ROI was determined by calculating the various both fixed costs was established and therefore variables, taking into account two factors the raw material and the various resources that are necessary for the making process seafood finally calculate both the Net Present Value (NPV) and Internal Rate of Return (IRR) was performed, proving the benefit that creates the restaurant, establishing its feasibility. The calculation of (VAN) reached is $ 29,628.20, also the calculation of (TIR) (47.7%) reflects the feasibility, establishing the feasibility of the creation of the seafood restaurant in the city of Windows, also established a period of three years to recover the investment. It is considered as the various studies both technical, and economic and performed last financial, to build the restaurant, it is significant to meet the expectations of demand Canton Windows, it is also necessary to establish advertising strategies to position the new restaurant seafood in the sector to attract and retain customers.